Burndown time of winter pastures and soybean grain yield - Ricce, Wilian da Silva; Alves, Sérgio José; Prete, Cássio Egídio Cavenaghi (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the effect of the winter pasture burndown time on soybean grain yield and on its components. The experiment was performed in an integrated crop-livestock area, in Campo Mourão, PR, Brazil, from 2002 to 2005 cropping seasons. A experimental design in randomized complete blocks, with eight replicates, was used. The treatments consisted of burndown at 30, 20, 10 and 0 days before sowing (DAS). Evaluations were done for: pasture dry matter at the sowing day; soybean plant height; number of plants per meter; number of pods per plant; number of grain per pod; weight of one thousand grains; and soybean yield. Burndown can be performed at 0, 10, 20 and 30 DAS without any damage to soybean grain productivity. Yield components tend to adjust to decrease grain productivity variations; the reduction on the number of plants per meter is compensated by higher number of pods per plant.